An integrated microchannel biosensor platform to analyse low density lactate metabolism in HepG2 cells in vitro. Issue 16 (19th March 2019) - Mi, Shengli; Xia, Jingjing; Xu, Yuanyuan; Du, Zhichang; Sun, Wei
Abstract : In this study, we developed an electrochemical microchannel biosensor platform to analyse lactate metabolism in cells. Abstract : In this study, we developed an electrochemical microchannel biosensor platform to analyse lactate metabolism in cells. This biosensor platform was fabricated by photolithography, thin-film deposition and microfluidic technology. A kind of functional biomaterial was prepared by mixing lactate oxidase, single-walled carbon nanotubes and chitosan, and platinum as working and blank electrodes of the biosensor was modified by a thin Prussian blue layer. The lactate biosensor was obtained by dropping functional biomaterials on the electrode. The results demonstrated that the sensitivity of the electrochemical biosensor was up to 567 nA mM −1 mm −2 and the limit of detection was 4.5 μM ( vs. Ag/AgCl as the counter/reference electrode). The biosensor used to quantitatively detect metabolic lactate concentrations in HepG2 cells cultured with cancer drugs showed high sensitivity, selectivity and stability, and has potential applications in organ-on-a-chip and tissue engineering technologies, which typically involve low concentrations of metabolites.